Improving adherence to guidelines for extended venous thromboembolism prophylaxis in patients with colorectal cancer. Issue 2 (26th November 2013) - Patel, Markand; Harris, Mark; Tapply, Ian; Longman, Rob
Abstract: Extended venous thromboembolism prophylaxis (EVTEP) with low-molecular weight heparin such as enoxaparin for 28 days following surgery for cancer significantly reduces venous thromboembolic events compared to a standard 6-10 day course. National Institute of Clinical Excellence (NICE) guidelines suggest EVTEP should be offered to patients undergoing colorectal cancer surgery. Local EVTEP prescribing and monitoring guidelines in a busy inner city teaching hospital colorectal surgery unit, were devised to ensure NICE guidelines are followed. Adherence to local EVTEP guidelines was recorded through a retrospective audit of patients undergoing elective colorectal cancer surgery during February 2011 (n=19). Prospective re-audit cycles were undertaken during April-May (n=17) and September-December 2012 (n=17). The first audit cycle revealed that overall standards were not being met with just 11% of 'at risk' patients being correctly identified in pre-operative assessment clinic and continued low adherence to guidelines on the ward with only 44% of patients being prescribed EVTEP at discharge. Following each audit cycle, educational interventions were directed towards the multi-disciplinary team involved in the care of patients undergoing colorectal cancer surgery. This involved education of the team members regarding EVTEP, presentation of the audit results with instruction for improvement. Results of the second and third audit cycles showed improvements in guideline adherence with 100% of patients in these cohorts having been prescribed EVTEP at discharge. Marked improvements were also seen in the correct identification of 'at risk' patients, patient education in pre-operative assessment clinic, and warning of potential side-effects. This project has shown a significant global improvement in EVTEP-related patient care and adherence to local guidelines following education of the multi-disciplinary team involved, which consequently reduced the risk of venous thromboembolism within this patient cohort.